2018
DOI: 10.1021/acs.biochem.8b00603
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Enzyme Stability and Activity through Hydrogen Bond-Enhanced Halogen Bonds

Abstract: The construction of more stable proteins is important in biomolecular engineering, particularly in the design of biologics-based therapeutics. We show here that replacing the tyrosine at position 18 (Y18) of T4 lysozyme with the unnatural amino acid m-chlorotyrosine (mClY) increases both the thermal stability (increasing the melting temperature by ∼1 °C and the melting enthalpy by 3 kcal/mol) and the enzymatic activity at elevated temperatures (15% higher than that of the parent enzyme at 40 °C) of this classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
89
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 91 publications
(166 reference statements)
3
89
0
Order By: Relevance
“…Halogen bonding (D-X• • • Y) is one important type of non-covalent interaction between a donor halogen atom X (F, Cl, Br or I) and an electron-rich atom/group Y (e.g., atoms with lone pair electrons including N, O, P and S) [1]. With its great bond strength tunability, halogen bonding has gained popularity in drug design [2][3][4][5], enzyme engineering [6], material science [7][8][9], catalysis [10][11][12][13] and crystal engineering [14][15][16]. The currently well-accepted understanding of halogen bonding focuses on the interplay of the following contributions: (1) charge transfer from nucleophile Y to the σ * anti-bonding orbital of D-X, (2) attractive electrostatic forces, (3) dispersion interaction, and (4) a repulsive term arising from Pauli exclusion principle.…”
Section: Introductionmentioning
confidence: 99%
“…Halogen bonding (D-X• • • Y) is one important type of non-covalent interaction between a donor halogen atom X (F, Cl, Br or I) and an electron-rich atom/group Y (e.g., atoms with lone pair electrons including N, O, P and S) [1]. With its great bond strength tunability, halogen bonding has gained popularity in drug design [2][3][4][5], enzyme engineering [6], material science [7][8][9], catalysis [10][11][12][13] and crystal engineering [14][15][16]. The currently well-accepted understanding of halogen bonding focuses on the interplay of the following contributions: (1) charge transfer from nucleophile Y to the σ * anti-bonding orbital of D-X, (2) attractive electrostatic forces, (3) dispersion interaction, and (4) a repulsive term arising from Pauli exclusion principle.…”
Section: Introductionmentioning
confidence: 99%
“…Often, the misincorporation mass spectrometry peaks are hidden by the dominant ncAA-incorporated peak [18,19], or mass spectra are provided but not deconvoluted and/or quantified [18,20]; otherwise, the deconvoluted spectra are poorly resolved due to the low sensitivity of the LCMS [21,22]. In many others, no supporting mass spectra data are provided at all, giving no information on the level of misincorporation in the presence of ncAA [23][24][25][26][27][28]. Incorporation fidelity is a factor that should not be ignored for enzyme activity, ligand binding or protein stability studies, since heterogeneity is almost always unavoidable in ncAA-incorporation studies, and may hide the true performance of the ncAA-incorporated species.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a handful of studies have successfully improved [26,27,35] or introduced novel catalytic function [18,28], or enhanced thermostability [19,25] via sitespecific ncAA incorporation, and even less introduced them into an active-site. While the latter study [25] observed both a 1% increase in T m and a modest 15% improvement in catalytic activity at 40°C relative to wild-type, the thermostable mutant was less-active than the wild-type at 23°C, which suggested the improved activity reflected only the improved thermostability at 40°C rather than a genuine improvement in catalysis. To our knowledge, we therefore report the first example of a genetically encoded, sitespecific active-site ncAA-incorporated variant with both enhanced activity at 22°C and thermostability (T m ), and demonstrate the benefits of including ncAAs in site-specific, smart designer libraries.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, numerous studies have reported the positive cooperativity between halogen bonds and hydrogen bonds (Li et al, 2008;Grabowski, 2013;Wu et al, 2013;Esrafili and Mousavian, 2017;Esrafili and Vakili, 2017;Carlsson et al, 2018) as well as the effects of the substituents on the cooperativity of halogen bonds (Solimannejad et al, 2013). In view of the potential application prospects of halogen bonds in the field of drug design, Adasme-Carreno et al (2016) performed calculations on 126 complexes of drug-like molecules; consequently, a positive cooperativity effect was observed in N-methylacetamide complexes with di-, tri-, and tetrafluoroiodobenzenes, which led to the strengthening of halogen bonds.…”
Section: Introductionmentioning
confidence: 99%